High-entropy oxide catalyst with zinc-iron spinel structure as well as preparation method and application of high-entropy oxide catalyst

By solidly resolving a variety of metal components, the zinc iron spinel high-entropy oxide catalyst is solved, and the problem of insufficient activity of traditional catalysts under mild conditions is achieved, and the high activity and selective CO2 hydrogenation is achieved to produce olefins, and simplify the It is suitable for industrial applications.

CN119281347APending Publication Date: 2025-01-10CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411541671.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional spinel oxide catalysts have insufficient catalytic activity and olefin selectivity under mild conditions, and there are problems of high reaction temperature and high cost in the development of high entropy catalyst materials.

Method used

By solidly dissolving a variety of metal components, a single-phase stable zinc-iron spinel high-entropy oxide catalyst is formed, and prepared by precipitation-hydrothermal method, combined with hydrogen reduction and sodium salt support, calcination forms a catalyst with high activity and selectivity. .

Benefits of technology

The catalytic activity and selectivity are significantly improved under mild conditions, the CO2 conversion rate and olefin selectivity are excellent, suitable for industrial applications, and the process is simple and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281347A_ABST
    Figure CN119281347A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst materials, and discloses a high-entropy oxide catalyst with a zinc-iron spinel structure as well as a preparation method and application of the high-entropy oxide catalyst. The preparation method comprises the following steps: dissolving five different metal salts in deionized water, and slowly adding an ammonium hydroxide solution; carrying out hydrothermal treatment on the solution, washing and drying to obtain a catalyst precursor; and finally, loading sodium onto the prepared catalyst by using an impregnation method, and calcining to obtain the high-entropy spinel catalyst with the zinc-iron structure. The catalyst prepared by the invention has a large specific surface area and abundant active sites, and also has a stable crystal structure, so that the catalytic activity is enhanced. The preparation method is simple, low in cost and capable of being widely applied, and the final purpose is to efficiently and stably prepare high-value chemicals such as olefin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalyst materials, in particular to a high entropy oxide catalyst with a zinc-iron spinel structure and a preparation method and application thereof. Background Art

[0002] The current rapid economic development has led to global resource shortages and environmental degradation. Therefore, people have begun to focus on finding clean, sustainable, and alternative green energy. Fischer-Tropsch synthesis (FTS) is a key technology that can convert syngas (a mixture of H2 and CO2) from coal, natural gas or biomass into liquid fuels and high-value chemicals such as olefins, gasoline and diesel. To achieve this process, catalysts are needed as a medium to regulate the products.

[0003] Traditional iron-based catalysts are widely used in carbon dioxide hydrogenation catalysis due to their low price, wide adjustable temperature range and wide product distribution. However, traditional spinel oxide catalysts have limited exposed active sites and high reaction temperatures, making it difficult to obtain high catalytic activity and high selectivity for olefin products under mild conditions. High entropy catalyst materials are made of five-element metal solid solutions. Compared with traditional catalysts, they have higher structural stability and their own unique physical and chemical properties, such as element adjustability. By rationally adjusting the constituent elements of high entropy catalyst materials, high activity and high selectivity for olefins can be achieved, and they can be used in various catalytic aspects. At present, some multi-metal-promoted traditional iron-based catalysts have been applied for relevant patents for CO2 hydrogenation to synthesize low-carbon olefins. Patent CN114405537B proposes a cesium-modified cobalt ferrite multi-metal catalyst with a selectivity of 40% for low-carbon hydrocarbons, but the additive is cesium, which is expensive and the reaction temperature is high (320°C). Patent CN109675573A provides Na-modified Fe 100 Mn 25 Zn 25 The CO2 conversion rate of the catalyst is only 23.9%, and the reaction temperature reaches 330°C. Therefore, it is very important to develop a catalyst with high activity, high selectivity and mild reaction conditions in the process of hydrogenation of carbon dioxide to high carbon hydrocarbons. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a high entropy oxide catalyst with a zinc-iron spinel structure and a preparation method and application thereof. The present invention forms a single-phase stable high entropy spinel catalyst by solid dissolving a plurality of different metal components, thereby improving the catalytic activity of the catalyst. At the same time, the doping of metals with different valence states causes serious lattice distortion, effectively improves the specific surface area of ​​the catalyst, and increases the active components, thereby obtaining a catalyst material for CO2 hydrogenation to olefins with high activity, selectivity, stability and safety under relatively mild conditions.

[0005] The technical solution adopted by the present invention to solve its technical problem is:

[0006] A method for preparing a zinc-iron spinel structured high entropy oxide catalyst comprises the following steps:

[0007] Step S1, dissolving iron salt, copper salt, zinc salt, manganese salt and zirconium salt in deionized water, slowly adding 28% NH4OH solution and stirring evenly to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction; the hydrothermal reaction condition is 160-200°C;

[0008] Step S2, after the hydrothermal reaction is completed, the solution is cooled to room temperature, the solution after the reaction is collected, centrifuged and washed, and then placed in an oven for drying at a temperature of 100 to 140° C. for 10 to 14 hours to obtain a metal / polymer composite material;

[0009] Step S3, loading the dried metal / polymer composite material with sodium salt by an impregnation method;

[0010] Step S4, placing in a tubular furnace and calcining under argon conditions, the calcination temperature is 200-600° C., and maintained for 2-5 hours, and after calcination, a finished zinc-iron spinel structure high entropy oxide catalyst is obtained.

[0011] Further, in step S1, the iron salt is one or more of ferric chloride trihydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric sulfate pentahydrate, and ferric acetate tetrahydrate; the copper salt is one or more of copper chloride dihydrate, copper nitrate trihydrate, copper sulfate pentahydrate, and copper acetate monohydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, and zinc acetate dihydrate; the manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, and manganese acetate tetrahydrate; and the zirconium salt is one or more of zirconium chloride trihydrate, zirconium chloride octahydrate, and zirconium sulfate.

[0012] Furthermore, in step S1, the molar ratio of iron salt, copper salt, zinc salt, manganese salt and zirconium salt is 7:1:3:(0.5-0.66):(0.33-0.5).

[0013] Furthermore, in step S1, the reaction temperature of the hydrothermal reaction is 180° C. and the reaction time is 24 h.

[0014] Furthermore, in step S2, the drying temperature is 100° C. and maintained for 12 hours.

[0015] Furthermore, in step S3, the loading amount of the sodium salt is 1%.

[0016] Furthermore, in step S4, the calcination temperature is 400° C. and maintained for 3 hours.

[0017] A high entropy oxide catalyst with a zinc-iron spinel structure is prepared by adopting the preparation method.

[0018] An application of the above-mentioned zinc-iron spinel structured high entropy oxide catalyst, and an application of the zinc-iron spinel structured high entropy oxide catalyst in carbon dioxide hydrogenation catalysis.

[0019] Furthermore, the application is specifically as follows: after the zinc-iron spinel structured high entropy oxide catalyst is reduced with H2, it is loaded into a fixed fluidized bed, a mixed gas consisting of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 290°C and a pressure of 2MPa, wherein the molar ratio of CO2 to H2 is 1:3.

[0020] The beneficial effects of the present invention are as follows: the present invention has a reasonable design, a simple preparation method, and has the following advantages:

[0021] (1) The zinc-iron spinel structure high entropy oxide catalyst prepared by the present invention is prepared by precipitation-hydrothermal method, which has excellent preparation process conditions, and the raw materials are easy to obtain, which is conducive to large-scale production; at the same time, the content of the catalyst component can be optimized by the metal ratio in the high entropy, which is conducive to the synergistic effect of multiple elements and the formation and stability of the active phase; in addition, this method causes the surface of the synthesized catalyst to have a severely distorted lattice distortion through the solid solution of multiple elements, while increasing the specific surface area, more active sites (elemental Fe) can be exposed after hydrogen reduction;

[0022] (2) The zinc-iron spinel high entropy oxide catalyst prepared by the present invention shows good catalytic activity under relatively mild conditions, and both the CO2 conversion rate and the olefin selectivity are excellent, which can provide broad prospects for subsequent industrial applications and olefin production. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 is an X-ray powder diffraction (XRD) diagram of the catalyst after the reaction in Examples 1 to 3 and Comparative Examples 1 to 3;

[0025] Figure 2 is the X-ray powder diffraction (XRD) diagram of the fresh catalyst in Examples 1 to 3 and Comparative Examples 1 to 3;

[0026] Figure 3 is the morphology (TEM) of the fresh catalyst in Example 1;

[0027] Figure 4 is the N2 adsorption-desorption isotherm of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 3;

[0028] Figure 5 It is a graph showing the CO2 conversion rate of the catalysts in Examples 1 to 3 and Comparative Examples 1 to 3 changing with time. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A method for preparing a zinc-iron spinel structured high entropy oxide catalyst comprises the following steps:

[0033] A. Dissolve five different metal salt solutions in deionized water, stir for 10 minutes, then slowly add 28% NH4OH solution, and continue stirring for 1 hour to obtain a precipitated brown solution;

[0034] B. Place the above metal precursor solution into a reaction kettle, raise the temperature to 160-200°C and maintain for 24 hours;

[0035] C. After the reaction is completed, wait for the reactor to cool completely, wash the solution three times with deionized water and anhydrous ethanol by centrifugation, collect the sample after removing the surface solvent and put it into a culture dish;

[0036] D. Place the sample in the culture dish in an oven and dry it at 100-140°C for 10-14 hours;

[0037] E. Take the sample out of the reaction dish, add 200 ml of deionized water and stir, then drop the NaNO3 aqueous solution into it;

[0038] F. After the step is completed, the sample is placed in an oven for drying at 100°C for 12 hours;

[0039] G. Place the mixture in a tubular furnace into which argon gas is introduced and calcined at a temperature of 200 to 600° C., maintained for 2 to 5 minutes, at a rate of 5° C. / min, to finally obtain the finished catalyst material HEO.

[0040] Furthermore, the molar ratio of iron salt, copper salt, zinc salt, manganese salt and zirconium salt is 7:1:3:(0.5-0.66):(0.33-0.5).

[0041] The invention provides a zinc-iron spinel structured high entropy oxide catalyst, which is prepared by the above method.

[0042] The invention provides an application of a zinc-iron spinel structured high entropy oxide catalyst in chemical catalysis, specifically for catalyzing carbon dioxide and hydrogen under high temperature and high pressure to produce high-value chemicals, such as olefins.

[0043] The specific application is: used as a catalyst in the carbon dioxide hydrogenation reaction, first reduced for 18 hours at a temperature of 400°C, a pressure of 0.4MPa, and a space velocity of 1500ml / (g*h). After the reduction is completed, the catalyst is loaded into the reactor, and a CO2 / H2 mixed gas with a molar ratio of 1:3 is introduced, and hydrogenation is carried out to prepare olefins at a temperature of 290°C, a pressure of 2MPa, and a space velocity of 2500ml / (g*h). The reaction time is 75 hours.

[0044] Example 1

[0045] A method for preparing a zinc-iron spinel structured high entropy oxide catalyst comprises the following steps:

[0046] A. Fe(NO3)3·9H2O (7.07 g), Cu(NO3)2·6H2O (2.23 g), Mn(NO3)2·6H2O (0.31 g), CuCl2·2H2O (0.42 g), and ZrO(NO3)2·xH2O (0.289 g) were dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Cu:Zn:Mn:Zr was 7:1:3:0.5:0.5); after stirring for 10 minutes, 9 ml of 28% NH4OH solution was slowly added and stirring was continued for 1 hour;

[0047] B. Place the above metal precursor solution into a reaction kettle and keep it at 180°C for 24 hours;

[0048] C. After the reaction is completed, wait for the reactor to cool completely, centrifuge and wash the solution three times with deionized water and anhydrous ethanol, collect the sample after removing the surface solvent and put it into a culture dish;

[0049] D. Place the sample in the culture dish in an oven and dry it at 100°C for 12 hours;

[0050] E. Take out the sample from the reaction dish, take out 1.2g, add 200ml of deionized water and stir, then drop 0.047g of NaNO3;

[0051] After steps F and E, the samples were placed in an oven for drying at 100°C for 12 h.

[0052] G. Place in a tubular furnace with argon gas and calcine at 400°C for 4 hours at a rate of 5°C / min. Finally, the catalyst material HEO-Mn1 is obtained.

[0053] Experimental operation steps of the catalytic evaluation system: First, weigh the catalyst material and quartz sand as needed and mix them evenly. Then, disassemble the reaction tube in the high-pressure catalytic evaluation system, put a small amount of quartz wool and quartz sand in it from top to bottom, put the catalyst in after the height of the quartz sand reaches half of the height, and then put the quartz sand in until the top of the reaction tube, and finally fill a small amount of quartz sand on the top. Tighten the screws of each part and reconnect it to the high-pressure catalytic evaluation system. Make sure that the entire system is leak-proof. First, the above-mentioned catalyst is reduced by hydrogen, specifically: first reduced by H2, the reduction conditions are 0.4MPa pressure, temperature 400℃, air velocity 1500ml / (g*h), after 18h, and used for subsequent catalytic reactions after reduction. After the reduction is completed, the catalyst is loaded into the reactor, and a CO2 / H2 mixed gas with a molar ratio of 1:3 is introduced. Hydrogenation to prepare olefins is carried out at a temperature of 290℃, a pressure of 2MPa, and an air velocity of 2500ml / (g*h). The reaction time is 75h.

[0054] The average data within 75 hours was calculated and the CO2 conversion rate of the catalyst was 38.9%, the CH4 selectivity was 21.97%, and the C2 = -C4 = The selectivity is 40.7%, C5 + The selectivity is 30.24%.

[0055] Example 2

[0056] The difference from Example 1 is: Step A in this example is: A. Fe(NO3)3·9H2O (7.07 g), Zn(NO3)2·6H2O (2.23 g), Mn(NO3)2·6H2O (0.31 g), CuCl2·2H2O (0.42 g), and ZrO(NO3)2·xH2O (0.231 g) are dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Cu:Zn:Mn:Zr is 7:1:3:0.6:0.4); after stirring for 10 minutes, 9 ml of 28% NH4OH solution is slowly added, and stirring is continued for 1 hour.

[0057] In this embodiment, the catalyst material HEO-Mn 1.5 .

[0058] The catalytic reaction process was the same as in Example 1. The average data within 75 hours was calculated to obtain a CO2 conversion rate of 40.9%, a CH4 selectivity of 25.6%, and a C2 = -C4 = The selectivity is 35.15%, C5 + The selectivity is 33.57%.

[0059] Example 3

[0060] The difference from Example 1 is: Step A in this example is: A. Fe(NO3)3·9H2O (7.07 g), Zn(NO3)2·6H2O (2.23 g), Mn(NO3)2·6H2O (0.31 g), CuCl2·2H2O (0.42 g), and ZrO(NO3)2·xH2O (0.192 g) are dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Cu:Zn:Mn:Zr is 7:1:3:0.66:0.33); after stirring for 10 minutes, slowly add 9 ml of 28% NH4OH solution and continue stirring for 1 hour.

[0061] In this embodiment, the catalyst material HEO-Mn2 is finally obtained.

[0062] The catalytic reaction process was the same as in Example 1. The average data within 75 hours was calculated to obtain a CO2 conversion rate of 41.3%, a CH4 selectivity of 19.2%, and a C2 = -C4 = The selectivity is 37.3%, C5 + The selectivity is 38.49%.

[0063] Comparative Example 1

[0064] The difference from Example 1 is that the metal element is reduced in step A of this comparative example, specifically:

[0065] A. Dissolve Fe(NO3)3·9H2O (8.08 g) and Zn(NO3)2·6H2O (2.96 g) in 60 ml of deionized water (wherein the molar ratio of Fe:Zn is 2:1); after stirring for 10 minutes, slowly add 9 ml of 28% NH4OH solution and continue stirring for 1 hour.

[0066] This comparative example finally obtained the catalyst material ZnFe2O4.

[0067] The catalytic reaction process was the same as in Example 1. The average data within 75 hours was calculated to obtain a CO2 conversion rate of 29.7%, a CH4 selectivity of 23.37%, and a C2 = -C4 = The selectivity is 39.8%, C5 + The selectivity is 30.29%.

[0068] Comparative Example 2

[0069] The difference from Example 1 is that in step A of this comparative example, Mn is replaced by Co, specifically:

[0070] A. Fe(NO3)3·9H2O (7.07 g), Zn(NO3)2·6H2O (2.23 g), Co(NO3)2·6H2O (0.36 g), CuCl2·2H2O (0.42 g), and ZrO(NO3)2·xH2O (0.289 g) were dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Cu:Zn:Co:Zr is 7:1:3:0.5:0.5); after stirring for 10 minutes, 9 ml of 28% NH4OH solution was slowly added and stirring was continued for 1 h.

[0071] The catalyst material HEO-Co was finally obtained in this comparative example.

[0072] The catalytic reaction process was the same as in Example 1. The average data within 75 hours was calculated to obtain a CO2 conversion rate of 45.1%, a CH4 selectivity of 39.69%, and a C2 = -C4 = The selectivity is 3.88%, C5 + The selectivity is 13.35%.

[0073] Comparative Example 3

[0074] The difference from Example 1 is that in step A of this comparative example, Mn is replaced by Mg, specifically:

[0075] A. Fe(NO3)3·9H2O (7.07 g), Zn(NO3)2·6H2O (2.23 g), Mg(NO3)2·6H2O (0.32 g), CuCl2·2H2O (0.42 g), and ZrO(NO3)2·xH2O (0.289 g) were dissolved in 60 ml of deionized water (wherein the molar ratio of Fe:Cu:Zn:Co:Zr is 7:1:3:0.5:0.5); after stirring for 10 minutes, 9 ml of 28% NH4OH solution was slowly added and stirring was continued for 1 hour.

[0076] The catalyst material HEO-Mg was finally obtained in this comparative example.

[0077] The catalytic reaction process was the same as in Example 1. The average data within 75 hours was calculated to obtain a CO2 conversion rate of 35.4%, a CH4 selectivity of 28.05%, and a C2 = -C4 = The selectivity is 28.2%, C5 + The selectivity is 23.6%.

[0078] The catalytic performance of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested. The test results are shown in Table 1.

[0079] Table 1 Catalytic performance of Example 1 to Example 3 and Comparative Example 1 to Comparative Example 3

[0080]

[0081] Table 1 shows the average performance of the catalysts at different calcination temperatures within 75 hours. The conversion rate of CO2 of HEO-Mn1 of the present invention reaches 38.9%, the selectivity of carbon monoxide is only 10.8%, the selectivity of CH4 is 21.97%, and the selectivity of C2 = -C4 = The selectivity is 40.7%.

[0082] By comparing Example 1 with Examples 2 and 3, it can be seen that as the Mn content increases, the CO2 conversion rate increases from 38.9% to 41.3%, and the C5 + The selectivity of C2 increased from 30.24% to 38.49%, but = -C4 = The results show that the increase in Mn content leads to the conversion of short-chain hydrocarbons to long-chain hydrocarbons, which improves the + The selectivity of olefins is relatively low. Figure 1 , Table 1, Examples 1 to 3 show that too much Mn is more conducive to the formation of Fe5C2, thereby increasing C5 + Hydrocarbon selectivity reduces the yield of olefins. In addition, changing the composition of metal oxides has a great difference in the yield of olefins. For HEO-Co in Comparative Example 2, although the conversion rate of CO2 reached 45.1%, its O / P was only 0.09. For HEO-Mg in Comparative Example 3, the conversion rate of CO2 reached 35.4% and the O / P was 1.41. This shows that high entropy catalysts with different elements in solid solution have different selectivity for products, and the highest yield of olefins for HEO-Mn1 is 0.0487. Regarding Comparative Example 1, the performance test of traditional ZnFe2O4 was also performed. Its conversion rate for CO2 is 29.7%, which is less than 38.9% of HEO-Mn1 and the yield of olefins is much less than that of HEO-Mn1. Therefore, in summary, HEO-Mn1 has the best catalytic activity and high olefin selectivity.

[0083] Figure 2 The XRD patterns of various catalysts are shown. From the figure, we can see that the diffraction peak of traditional ZnFe2O4 is high and sharp, while the diffraction peak of the high entropy catalyst formed by mixing different elements is significantly weakened and broadened, indicating that the crystallization of high entropy oxides of zinc-iron structure is suppressed, which indirectly reflects the larger specific surface area. In addition, Figure 3 The actual morphology of HEO-Mn1 is shown, indicating the successful synthesis of zinc-iron structured high entropy oxides. Figure 4The isothermal adsorption-desorption curves show their specific surface areas. Among them, HEO-Mn1 has the largest surface area of ​​75.71 m 2 ·g -1 . This confirms Figure 2 The XRD results show that the rich specific surface area provides more active sites and improves the catalytic activity of the sample. Finally, after 75 hours of continuous carbon dioxide hydrogenation reaction, the prepared catalyst has good stability in catalyzing the hydrogenation of carbon dioxide to produce light olefins ( Figure 5 ) and practical application potential.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high entropy oxide catalyst of a zinc-iron spinel structure, characterized in that: The specific steps include: Step S1, dissolving iron salt, copper salt, zinc salt, manganese salt and zirconium salt in deionized water, slowly adding 28% NH4OH solution and stirring evenly to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction; the hydrothermal reaction condition is 160-200°C; Step S2, after the hydrothermal reaction is completed, the solution is cooled to room temperature, the solution after the reaction is collected, centrifuged and washed, and then placed in an oven for drying at a temperature of 100 to 140° C. for 10 to 14 hours to obtain a metal / polymer composite material; Step S3, loading the dried metal / polymer composite material with sodium salt by an impregnation method; Step S4, placing in a tubular furnace and calcining under argon conditions, the calcination temperature is 200-600° C., maintained for 2-5 hours, and a finished high-entropy spinel catalyst with a zinc-iron structure is obtained after calcination.

2. The method for preparing a zinc-iron spinel high entropy oxide catalyst according to claim 1, characterized in that: In the step S1, the iron salt is one or more of ferric chloride trihydrate, anhydrous ferric chloride, ferric nitrate nonahydrate, ferric sulfate pentahydrate, and ferric acetate tetrahydrate; the copper salt is one or more of copper chloride dihydrate, copper nitrate trihydrate, copper sulfate pentahydrate, and copper acetate monohydrate; the zinc salt is one or more of zinc chloride tetrahydrate, zinc nitrate hexahydrate, zinc sulfate heptahydrate, and zinc acetate dihydrate; the manganese salt is one or more of manganese chloride tetrahydrate, manganese nitrate tetrahydrate, manganese sulfate tetrahydrate, and manganese acetate tetrahydrate; and the zirconium salt is one or more of zirconium chloride trihydrate, zirconium chloride octahydrate, and zirconium sulfate.

3. The method for preparing a zinc-iron spinel high entropy oxide catalyst according to claim 1, characterized in that: In the step S1, the molar ratio of the iron salt, the copper salt, the zinc salt, the manganese salt and the zirconium salt is 7:1:3:(0.5-0.66):(0.33-0.5).

4. The method for preparing a zinc-iron spinel structured high entropy oxide catalyst according to claim 1, characterized in that: In step S1, the reaction temperature of the hydrothermal reaction is 180° C. and the reaction time is 24 hours.

5. The method for preparing a zinc-iron spinel high entropy oxide catalyst according to claim 1, characterized in that: In step S2, the drying temperature is 100° C. and maintained for 12 hours.

6. The method for preparing a zinc-iron spinel structured high entropy oxide catalyst according to claim 1, characterized in that: In step S3, the loading amount of the sodium salt is 1%.

7. The method for preparing a zinc-iron spinel high entropy oxide catalyst according to claim 1, characterized in that: In the step S4, the calcination temperature is 400° C. and maintained for 3 hours.

8. A high entropy spinel catalyst of zinc-iron structure, characterized in that: The zinc-iron spinel structured high entropy oxide catalyst is prepared by the preparation method as claimed in any one of claims 1 to 7.

9. An application of a zinc-iron spinel structured high entropy oxide catalyst as claimed in claim 8, characterized in that: The application of the zinc-iron spinel structured high entropy oxide catalyst in carbon dioxide hydrogenation catalysis.

10. The use of a zinc-iron spinel structured high entropy oxide catalyst according to claim 9, characterized in that: The application is specifically as follows: a high entropy spinel catalyst with a zinc-iron spinel structure is reduced with H2, then loaded into a fixed fluidized bed, a mixed gas consisting of CO2 and H2 is introduced, and a hydrogenation reaction is carried out at a temperature of 290°C and a pressure of 2MPa, wherein the molar ratio of CO2 to H2 is 1:3.

Citation Information

Patent Citations

  • Catalyst for preparing high-carbon alpha-olefin by hydrogenation of carbon dioxide, and preparation method and application

    CN109675573A

  • A Cs-modified cobalt ferrite molecular sieve multifunctional catalyst, its preparation method and application

    CN114405537B